Psychological self-regulation of rheumatic patients with different types of illness perception - V. M. Yaltonsky; I. N. Abrosimov; N. A. Sirota (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Purpose. The purpose of the study is to describe the basic profiles of perception of rheumatic diseases and a comparative analysis of negative emotional response to the disease, coping behavior and adherence to treatment as parameters of psychological self-regulation in groups of patients with different types of perception of the disease.Materials and methods. 160 women with rheumatic diseases undergoing hospital treatment were examined: 60 with systemic lupus erythematosus, 50 with rheumatoid arthritis, 50 with systemic scleroderma. Average age—34.00±17.46 years. The study was conducted based on Research Institute of Rheumatology named after. V.A. Nasonova.Results. During the study, basic profiles of disease perception were described, and on their basis, groups of patients with different types of disease perception were identified: group 1—unformed perception of the disease, group 2—positive perception of disease control, group 3—negative perception of the disease threat. A comparative analysis of the parameters of psychological self-regulation in three groups showed that anxiety and depression were less pronounced in the group with an unformed perception of the disease than in the other two groups. At the same time, the coping strategies “Self-control” and “Planning to solve problems” are statistically significantly higher in the group of patients with a positive perception of the possible control of their disease. The level of adherence to treatment was statistically significantly higher in the group of patients with a positive perception of the controllability of the disease.Conclusion. Indicators of psychological self-regulation are specific in groups of patients with different types of perception of rheumatic disease. The identification of basic profiles and a description on their basis of the types of perception of rheumatic disease complement the existing data on the mechanisms of personality adaptation to the disease, and expand the possibilities of psychological support for the treatment and rehabilitation of patients with rheumatic diseases.